2018
DOI: 10.1016/s2468-2667(18)30045-8
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in childhood and adolescent body-mass index, weight, and height from 1953 to 2015: an analysis of four longitudinal, observational, British birth cohort studies

Abstract: SummaryBackgroundSocioeconomic inequalities in childhood body-mass index (BMI) have been documented in high-income countries; however, uncertainty exists with regard to how they have changed over time, how inequalities in the composite parts (ie, weight and height) of BMI have changed, and whether inequalities differ in magnitude across the outcome distribution. Therefore, we aimed to investigate how socioeconomic inequalities in childhood and adolescent weight, height, and BMI have changed over time in Britai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
160
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 170 publications
(177 citation statements)
references
References 42 publications
12
160
1
4
Order By: Relevance
“…However, as detailed dietary measures were not available in the MCS, we were not able to fully investigate this. In addition, we found, as suggested by previous studies, that BMI disparities at 14 years were greater at higher end of the BMI distribution in the White and South Asian groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, as detailed dietary measures were not available in the MCS, we were not able to fully investigate this. In addition, we found, as suggested by previous studies, that BMI disparities at 14 years were greater at higher end of the BMI distribution in the White and South Asian groups.…”
Section: Discussionsupporting
confidence: 89%
“…In many higher‐income countries, levels of body mass index (BMI) and obesity are socially patterned, with disadvantaged population groups having higher mean BMI and more likely to be affected by obesity, possibly because of their disproportionally greater exposure to risk factors such as consumption of energy‐dense foods . Recent evidence also suggests that socio‐economic differences in BMI have widened across generations and are emerging at younger ages . High BMI in childhood tends to track into adulthood, and adult obesity is associated with a number of health outcomes, especially cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, obesity disproportionally affects individuals from lower social classes, and this is particularly the case for women . Recent research showed how socioeconomic disparities in child and adolescent body weight have reversed over time; in the 1940s through to the 1970s, low SES was associated with lower weight; however, in 2001, low SES was associated with higher weight. The reason for this socioeconomic disparity is not well understood, but it is often attributed to the greater availability of low‐cost, calorie‐dense foods in more deprived areas relative to more affluent neighborhoods .…”
Section: Introductionmentioning
confidence: 99%
“…But children and adolescents of low socioeconomic status born in 2001 were more likely to be heavier. The inequalities in body mass index (BMI) widened as millennials reached adolescence and in those with higher BMI …”
Section: Diseases Of Povertymentioning
confidence: 99%